Syria: Between its Virtues Morality According to the Sacred Text and Geopolitical Conflict - Muh. Syaifudin; Bakr Zaki Awad (Proceeding Of The International Seminar and Conference on Global Issues, 2016)
This article aims to reveal the extent of the validity of the sacred texts of Islam, the traditions of the prophet about the primacy of the nation of Syria on the one hand, and the current conflict impressive this nation as one nation accused by some parties.Writing this article uses descriptive analysis method to analyze the text of the traditions of the prophet either textual or contextual, also using a functional approach. The authors chose this approach because of the actors who played in the conflict in Syria is more appropriate to say, playing for the function or interests that are temporary. This is evidenced by the difference of their attitude to the case and other regions, outside Syria.Resultsthat writer get from search two sides, namely the text of the hadith and the circumstances of the real Syrian conflict is that the texts are not only meaningful, but the systemic. Thus cannot be said that an attack on Syria, even by Muslims themselves, considered denial of the traditions of the Prophet. That is true whether or not the attack on Syria must be seen from the case itself in terms of Islamic law. Keywords: Syria, virtues morality, geopolitical conflict